Images Are Data: A Breast Imaging Perspective on a Contemporary Paradigm - Dietzel, Matthias; Clauser, Paola; Kapetas, Panagiotis; Schulz-Wendtland, Rüdiger; Baltzer, Pascal Andreas Thomas (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Background Considering radiological examinations not as mere images, but as a source of data, has become the key paradigm in the diagnostic imaging field. This change of perspective is particularly popular in breast imaging. It allows breast radiologists to apply algorithms derived from computer science, to realize innovative clinical applications, and to refine already established methods. In this context, the terminology imaging biomarker, radiomics, and artificial intelligence are of pivotal importance. These methods promise noninvasive, low-cost (e.g., in comparison to multigene arrays), and workflow-friendly (automated, only one examination, instantaneous results, etc.) delivery of clinically relevant information. Methods and Results This paper is designed as a narrative review on the previously mentioned paradigm. The focus is on key concepts in breast imaging and important buzzwords are explained. For all areas of breast imaging, exemplary studies and potential clinical use cases are discussed. Conclusion Considering radiological examination as a source of data may optimize patient management by guiding individualized breast cancer diagnosis and oncologic treatment in the age of precision medicine. Key Points: In conventional breast imaging, examinations are interpreted based on patterns perceivable by visual inspection. The radiomics paradigm treats breast images as a source of data, containing information beyond what is visible to our eyes. This results in radiomic signatures that may be considered as imaging biomarkers, as they provide diagnostic, predictive, and prognostic information. Radiomics derived imaging biomarkers may be used to individualize breast cancer treatment in the era of precision medicine. The concept and key research of radiomics in the field of breast imaging will be discussed in this narrative review. Citation Format Dietzel M, Clauser P, Kapetas P etal. Images Are Data: A Breast Imaging Perspective on a Contemporary Paradigm. Fortschr Röntgenstr 2021; DOI: 10.1055/a-1346-0095.
CRIS-Team Scopus Importer:2021-02-26
Keywords: artificial intelligence; breast; mammography; MR imaging; screening; ultrasound